2007
DOI: 10.1103/physrevb.76.235112
|View full text |Cite
|
Sign up to set email alerts
|

Metanematic transitions in a bilayer system: Application to the bilayer ruthenate

Abstract: It was suggested that the two consecutive metamagnetic transitions and the large residual resistivity discovered in Sr 3 Ru 2 O 7 can be understood via the nematic order and its domains in a single layer system. However, a recently reported anisotropy between two longitudinal resistivities induced by tilting the magnetic field away from the c axis cannot be explained within the single layer nematic picture. To fill the gap in our understanding within the nematic order scenario, we investigate the effects of bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
(48 reference statements)
2
49
0
Order By: Relevance
“…Thus, the elaborate model adopted in this paper is necessary for the description of the EO state. Although the antiferro stacking of the d-wave nematic order has been studied, 27,28 some essential factors have been neglected. Figure 4 shows the pronounced spin splitting in the 3 rd and 4 th bands.…”
Section: Antiferro Stacking: Electric Octupole Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the elaborate model adopted in this paper is necessary for the description of the EO state. Although the antiferro stacking of the d-wave nematic order has been studied, 27,28 some essential factors have been neglected. Figure 4 shows the pronounced spin splitting in the 3 rd and 4 th bands.…”
Section: Antiferro Stacking: Electric Octupole Ordermentioning
confidence: 99%
“…On the other hand, we can consider the two multipole states distinguished by the symmetry when we take into account the bilayer structure in the unit cell. 27,28 One is the ferro stacking of quadrupoles in the bilayer, and the other is the antiferro stacking. When we regard the unit cell as a multimer, the former is classified into the EQ order, and the latter is the EO order that we focus on.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, broken symmetry phases arise due to electron-electron interactions, within the Landau-Fermi liquid description [4][5][6][7][8][9][10][11] . In some cases, such instabilities lead to nematic phases [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . A comprehensive review about nematic Fermi fluids with an extensive list of references could be found in Ref.…”
Section: Landau's Theory Of the Fermi Liquid (Fl)mentioning
confidence: 99%
“…It is striking that for the parallel modulated nematic state only ρ yy e becomes larger than ρ 0 , whereas ρ xx e remains largely unchanged from the isotropic value. This is in contrast to the pure nematic phase, where the conductivity along one lattice direction is smaller than along the other lattice direction, while the average of both is close to the isotropic conductivity, [11,12,34] resulting in one principal resistivity component smaller and the other larger than the isotropic resistivity ρ 0 .…”
mentioning
confidence: 74%